Proceedings of the 1st International Workshop on Crowd-Based Software Development Methods and Technologies 2014
DOI: 10.1145/2666539.2666566
|View full text |Cite
|
Sign up to set email alerts
|

How the crowd impacts commercial applications: a user-oriented approach

Abstract: As crowdsourcing has been applied to a variety of disciplines, e.g. marketing and operationalization, more and more scientists turn their sights to how the crowd innovate software engineering to produce high quality software. However, they mainly focus on the impacts brought by domain experts or experienced developers on developing and managing open source softwares, whereas how softwares are influenced by the ordinary people e.g. end users is seldom discussed and easily omitted. To fill up the research gaps, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…A series of studies have investigated the potential of crowdsourced software evolution and maintenance [19], [24], [29], [97], [98], [175], [178], [179], [183]- [188].…”
Section: Crowdsourcing For Software Evolution and Maintenancementioning
confidence: 99%
See 1 more Smart Citation
“…A series of studies have investigated the potential of crowdsourced software evolution and maintenance [19], [24], [29], [97], [98], [175], [178], [179], [183]- [188].…”
Section: Crowdsourcing For Software Evolution and Maintenancementioning
confidence: 99%
“…Also, evaluation of the proposed framework was performed on a socially adaptive messenger system. He et al [183] proposed a 'suggestion model' to encourage crowd users to become more closely involved in commercial software runtime adaptation. A prototype and several adaptation strategies were introduced in this study.…”
Section: Crowdsourced Software Evolutionmentioning
confidence: 99%
“…Table 1 depicts the references identified per type of testing. [3], [43], [44], [45], [46], [47], [48] Non-Functional Testing [32], [43], [44], (performance); [49] (vulnerability); [50] (privacy) Validation and Acceptance Testing [11], [34], [35], [36], Usability Testing/ User Experience [35], [41], [51], [52], [53], [54], [55], [56], [57] Quality of Experience [26], [58], [59], [60], [61], [62] Research in functional and verification testing demonstrated that even complex testing tasks such as the verification of cross-browser issues [46] or the reproduction of context-sensitive app crashes [45] are possible to be tested with the crowd. In this vein, also non-functional testing such as performance testing [32] is possible.…”
Section: Application Of Crowdsourced Software Testingmentioning
confidence: 99%
“…Research in this area has shown that usability testing with a crowd is feasible, produces reliable and high quality results [11,56], is cost efficient [53,56], and can help reduce critical usability testing obstacles such as resource constraints, limited understanding of the usability concept, and resistance to the adoption of usability practices [51]. In addition to that, scholars have developed several workflows and corresponding tools to use crowdsourced usability testing [35,54,55], including machine learning approaches to group similar responses and filter meaningless submissions to reduce workload for test managers [64].…”
Section: Application Of Crowdsourced Software Testingmentioning
confidence: 99%